2006
DOI: 10.2220/biomedres.27.69
|View full text |Cite
|
Sign up to set email alerts
|

Inhibitory action of eugenol compounds on the production of nitric oxide in RAW264.7 macrophages

Abstract: Effects of eugenol compounds on the production of nitric oxide (NO) in RAW264.7 macrophages were analyzed in relation to the anti-inflammatory action of these compounds. Eugenol and isoeugenol inhibited lipopolysaccharide (LPS)-dependent production of NO, which was due to the inhibition of protein synthesis of inducible nitric oxide synthase (iNOS). Isoeugenol showed the most effective inhibitory effect and eugenol was less effective. LPS-dependent expression of cyclooxygenase-2 (COX-2) protein was also inhibi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
32
0
1

Year Published

2006
2006
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 57 publications
(35 citation statements)
references
References 18 publications
2
32
0
1
Order By: Relevance
“…Peroxynitrite, produced by the reaction of NO with a superoxide radical, is a highly reactive nitrogen species showing toxic effects by oxidizing and nitrating cellular macromolecules (Moncada and Bolanos, 2006). Eugenol was found to inhibit the expression of inducible nitric oxide synthase (iNOS) and to decrease the production of NO, the powerful pro-inflammatory mediator (Li et al, 2006). The anti-inflammatory action of eugenol may be also attributed to its inhibitory effect on cyclooxygenase-2 and 5-lipoxygenase, the key enzymes in biosynthetic pathway of inflammatory prostaglandins and leukotrienes Raghavenra et al, 2006).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Peroxynitrite, produced by the reaction of NO with a superoxide radical, is a highly reactive nitrogen species showing toxic effects by oxidizing and nitrating cellular macromolecules (Moncada and Bolanos, 2006). Eugenol was found to inhibit the expression of inducible nitric oxide synthase (iNOS) and to decrease the production of NO, the powerful pro-inflammatory mediator (Li et al, 2006). The anti-inflammatory action of eugenol may be also attributed to its inhibitory effect on cyclooxygenase-2 and 5-lipoxygenase, the key enzymes in biosynthetic pathway of inflammatory prostaglandins and leukotrienes Raghavenra et al, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…However, the mechanisms responsible for the anti-ulcer effect of eugenol are not yet clear. It was reported that eugenol is an antioxidant (Tiku et al, 2004;Ito et al, 2005), vasorelaxant (Nangle et al, 2006), transient receptor potential vanilloid 1 (TRPV1) agonist (Yang et al, 2003), and inducible nitric oxide synthase (iNOS) inhibitor (Li et al, 2006) which may contribute to its gastroprotective effect. This encouraged us to conduct the present study in order to clarify the possible mechanisms underlying the protective effect of eugenol against indomethacin-induced gastric ulceration in rats.…”
Section: Introductionmentioning
confidence: 99%
“…NO upregulates the COX-2 expression through the cAMP-response element. Some antiinflammatory agents decreased NO production by inhibiting the expression of iNOS protein and further decreased COX-2 expression [8,9,33]. In addition, iNOS can bind and activate COX-2 [9].…”
Section: Discussionmentioning
confidence: 99%
“…The agent has sedative and anodyne effects, but concomitantly shows an irritant action (Sneddon and Glew, 1973). It also has antioxidant, anti-inflammatory and antiseptic properties (Li et al, 2006). The analgesic action of eugenol had long been attributed to its action as a non-specific counter-irritant.…”
Section: Introductionmentioning
confidence: 99%